Investigation on the shear joints failure with tensile loading for aluminum pins - Mohd Firdaus, Mohd Zaid (2009)
The use of pin joints is to connect two steel plates together and to support load together or alone. It has been extensively used in civil, mechanical and aircraft structures. Most of the available methods have been developed to estimate the loading capacity using side-edge distance but not the position of the pins using angle. In this paper, a research is developed to recommend the best position of pin group under in tensile loads based on the assumptions of angle and distance from centroid. The investigation is using Aluminum pins as connecter to joint two plates made of steel. The force applied on the side of plate and the Finite Element Analysis (ALGOR) as software to analysis the model. The analysis is use to find the lowest stress from four pins and that the first pins will fail. That means the pin can support lowest load than others pins. From the result, the pin closest to the load applied, not symmetry with other pin or alone and far from centroid axis are faster failed. As conclusion, The more close distance to centroid axis and other pins, to more higher maximum stress or the pin can support high load before it failed.